Perlindungan Hukum bagi Konsumen dalam Transaksi Jual Beli Online Ditinjau dari Undang-Undang Nomor 1 Tahun 2024 tentang Perubahan Kedua Atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik - Jericho Owen Geraldo Manalu (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The rapid development of e-commerce in Indonesia makes transactions easier for consumers, but also presents various losses, such as fraud, goods that do not match the description, leaks of personal data, and problems with returning goods. In this context, Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) exists as a legal basis which is expected to provide protection for consumers in online buying and selling transactions. This research aims to explore and analyze the effectiveness of the legal protection provided by the ITE Law for consumers, with a focus on protection for detrimental transactions, consumer personal data, as well as dispute resolution mechanisms. The research method used is a normative approach with a literature study of statutory regulations and related legal literature. The research results show that the ITE Law provides quite comprehensive legal protection, including the obligation of electronic system operators to ensure the security of transactions and personal data, as well as regulating sanctions for perpetrators of fraud. However, even though regulations already exist, implementation and consumer understanding of their rights is still a major challenge.